Fabrication and characterization of fly ash-based geopolymer and its performance for immobilization of heavy metal cations - Iqbal, Rendy Muhamad; Supriadi, Warih; Burhan, R.Y. Perry; Nurherdiana, Silvana Dwi; Hidayati, Ririn Eva; Subaer, Subaer; Bayuaji, Ridho; Fansuri, Hamzah (Communications in Science and Technology, 2022)
In this study, the geopolymer from fly ash as based-raw material has been examined on the ability of several heavy metal ions immobilization. The fly ash has been provided from PT IPMOMI which firstly analyzed the physical and chemical properties. Fly ash and heavy metals were mixed with an activator base until homogeneous, then cast into a cylindrical shape mold following ASTM C 39-86 and left for 7 days. After that, the geopolymer was characterized by SEM, FTIR, XRD, compressive strength test and TCLP. The diffractogram of PT. IPMOMI fly ash exhibited the existence of mullite, alumina and iron oxide phase, which were suitable with XRF result. From FTIR spectra, the vibration on finger print area appeared indicating the vibration of T-O-T from geopolymer network. The observation revealed that the addition of Pb2+ cations caused microcracking from SEM image and affected the compressive strength of the geopolymer. Sr2+ was an ion that was very easilyleached compared to other three ions, and it caused a weak interaction between Sr2+ and geopolymer network. The higher amount of metal ions into the geopolymer network reduced the compressive strength of geopolymer. Sr2+-geopolymer had a lower compressive strength compared to Pb2+, Cd2+, and Co2+.